The hTERT Promoter Enhances the Antitumor Activity of an Oncolytic Adenovirus under a Hypoxic Microenvironment - Hashimoto, Yuuri (Public Library of Science, 2012)
Hypoxia is a microenvironmental factor that contributes to the invasion, progression and metastasis of tumor cells. Hypoxic tumor cells often show more resistance to conventional chemoradiotherapy than normoxic tumor cells, suggesting the requirement of novel antitumor therapies to efficiently eliminate the hypoxic tumor cells. We previously generated a tumor-specific replication-competent oncolytic adenovirus (OBP-301: Telomelysin), in which the human telomerase reverse transcriptase (hTERT) promoter drives viral E1 expression. Since the promoter activity of the hTERT gene has been shown to be upregulated by hypoxia, we hypothesized that, under hypoxic conditions, the antitumor effect of OBP-301 with the hTERT promoter would be more efficient than that of the wild-type adenovirus 5 (Ad5). In this study, we investigated the antitumor effects of OBP-301 and Ad5 against human cancer cells under a normoxic (20% oxygen) or a hypoxic (1% oxygen) condition. Hypoxic condition induced nuclear accumulation of the hypoxia-inducible factor-1α and upregulation of hTERT promoter activity in human cancer cells. The cytopathic activity of OBP-301 was significantly higher than that of Ad5 under hypoxic condition. Consistent with their cytopathic activity, the replication of OBP-301 was significantly higher than that of Ad5 under the hypoxic condition. OBP-301-mediated E1A was expressed within hypoxic areas of human xenograft tumors in mice. These results suggest that the cytopathic activity of OBP-301 against hypoxic tumor cells is mediated through hypoxia-mediated activation of the hTERT promoter. Regulation of oncolytic adenoviruses by the hTERT promoter is a promising antitumor strategy, not only for induction of tumor-specific oncolysis, but also for efficient elimination of hypoxic tumor cells.